Bridging the Gap Between Theory and Practice: A Problem-Based Learning Approach to Management Accounting in Indonesia - Saraswati, Rr Sri; Hapsari, Dini Wahjoe; Budiharjo, Roy (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia (ADPEBI), 2025)
Purpose – This study investigates the implementation of Problem-Based Learning (PBL) to enhance student engagement and learning outcomes in a Management Accounting course at a private university in Indonesia. Methodology/approach – Through a Classroom Action Research (CAR) approach, this study involved six undergraduate classes (N = 233 students), integrating PBL activities based on real-world business cases. Data collection included pre-tests, post-tests, structured classroom observations, and semi-structured student interviews. Findings – Results demonstrated significant improvements in students’ comprehension of accounting concepts, analytical problem-solving abilities, and active classroom participation. Thematic analysis further indicated that PBL fostered greater student motivation, confidence, and collaborative learning skills. Novelty/value – This study applies Problem-Based Learning in an advanced Management Accounting course—rarely explored in Indonesia. It combines quantitative and qualitative methods to demonstrate improved student engagement, critical thinking, and learning outcomes, offering a structured model adaptable for local accounting education. Keywords: Problem-Based Learning, Management Accounting, Classroom Action Research, Active Learning, Higher Education, Indonesia